Reasons for migration, parental acculturation, and language: the case of Chinese American and Mexican American parents and dual language learners - Buttiler, Maria Belen; Zhou, Qing; Uchikoshi, Yuuko (Frontiers in Psychology, 2023)
Migration is a complex process associated with a range of social, economic, and political reasons. In the U.S., almost one-quarter of the total population of parents are immigrant parents of children ages 0 to 10. Immigrant parents transmit values from their culture of origin as well as their language to their children. Additionally, they may undergo a process of cultural and psychological change known as acculturation. Research has shown that acculturation can be linked to parenting styles and adolescents' psychological well-being and behavioral problems. However, little is known about the associations among immigrant parents' acculturation, their home language and literacy practices, and their bilingual children's language skills. This study explores the relationships among reasons for migration, parental acculturation, home language and literacy practices, and child expressive vocabulary in English and their heritage language (HL). A group of 190 Spanish-English (N = 66) and Chinese-English (N = 124) dual language learners (DLLs) (mean age = 48.98 months) and their Chinese and Mexican parents (mean age of migration = 21.38 years old) participated. Results revealed that Mexican American families migrated to the U.S. mostly for multiple reasons, including joining family members, getting married, and looking for better education or job opportunities, whereas most Chinese American families migrated for family reasons only. Path analysis models showed that, for both cultural groups, language input in Spanish and Chinese mediated the relationship between parents' cultural orientations and DLLs' HL expressive vocabulary. These findings emphasize that despite the heterogeneity of immigrant families and the variability in DLLs' vocabulary skills in preschool, there exist some similarities across immigrant parents and bilingual children. A deeper understanding of acculturation practices and home language use can help educators better support children from diverse backgrounds and promote cultural awareness and sensitivity in the classroom.